2012
DOI: 10.1016/j.rmed.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of pulmonary rehabilitation and chest physiotherapy versus chest physiotherapy alone in bronchiectasis

Abstract: Pulmonary rehabilitation in addition to regular chest physiotherapy, improves exercise tolerance and health related quality of life in non cystic fibrosis bronchiectasis and the benefit was sustained at 12 weeks post end of pulmonary rehabilitation. Clinical trials regn no. NCT00868075.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 25 publications
5
83
0
6
Order By: Relevance
“…ESWT is responsive to pulmonary rehabilitation in patients with COPD (the pooled mean of studies in figure 9 is ∼360 s), bronchiectasis [203] and IPF [175] (table 3). ESWT is also responsive to oxygen therapy in patients with COPD [204] and IPF [175] who desaturate during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…ESWT is responsive to pulmonary rehabilitation in patients with COPD (the pooled mean of studies in figure 9 is ∼360 s), bronchiectasis [203] and IPF [175] (table 3). ESWT is also responsive to oxygen therapy in patients with COPD [204] and IPF [175] who desaturate during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, ONG et al [48] studied 95 patients with bronchiectasis, demonstrating a mean improvement in 6-min walk distance of 53 m which was sustained to 12 months (difference at 12 months 20.5 m) . A subsequent pilot randomised controlled trial showed improvements in LCQ and SGRQ sustained to 20 weeks after treatment [49]. In a recent randomised controlled trial by LEE et al [50], an 8-week supervised exercise training schedule that include airway-clearance techniques was compared with standard care .…”
Section: Airway Clearancementioning
confidence: 99%
“…Although few studies have explored the impact of physiotherapy in bronchiectasis, airway clearance techniques seem to be safe and allow a better sputum expectoration with an increase in patients' quality of life [20]. Evidence on pulmonary rehabilitation is scarce; however, most of the studies demonstrated an increase in patients' performance and quality of life, and an increase of the time to the next exacerbation [21][22][23]. Both physicians and patients agreed that additional controlled trials of these interventions would be beneficial but that the priority may be in identifying methods that are accessible and that encourage adherence.…”
Section: Consensus Statementmentioning
confidence: 99%
“…>96% of respondents felt that their bronchiectasis could be better managed through having a self-management plan co-designed with their HCP, and access to physiotherapy/pulmonary rehabilitation, which also includes teaching them how to use techniques/equipment at home [1,22,40,68,69]. Self-management plans facilitated by good communication between patients and HCPs empower patients to manage and cope with their condition more confidently and independently [70,71].…”
Section: Condition Managementmentioning
confidence: 99%